Wealth index association with self-reported oral health between white and non-white older Brazilians - Orlando Luiz do Amaral Júnior; Maria Laura Braccini Fagundes; Gabriele Rissotto Menegazzo; Jessye Melgarejo do Amaral Giordani (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: This cross-sectional study aimed to identify the association between self-reported oral health status and a wealth index among white and non-white older adults in Brazil. Data from individual assessments of 9,365 Brazilians aged 50 years or older were analyzed. Poisson regression models were performed to estimate the prevalence ratio between wealth index and self-reported oral health among whites and non-whites adjusted for intermediate and proximal determinants. The total prevalence of poor self-reported oral health on white and non-white individuals was 41.6% (95%CI: 40.0-43.4) and 48% (95%CI: 47.1-49.8) respectively. The adjusted analysis showed that, for whites, the wealth index is associated with self-reported oral health since individuals in the 3rd, 4th, and 5th quintiles have 25% (PR = 0.75; 95%CI: 0.65-0.88), 20% (PR = 0.80; 95%CI: 0.67-0.95), and 39% (PR = 0.61; 95%CI: 0.50-0.75) lower prevalence of poor self-reported oral health than those in the poorest quintile. For non-white individuals, the wealth index is associated with self-reported oral health only for those in the 5th quintile, with 25% (PR = 0.85; 95%CI: 0.72-0.99) lower prevalence of poor self-reported oral health than those in the poorest quintile. The wealth index showed different effects on self-reported oral health among whites and non-whites. Socioeconomic status indicators may reflect racial inequalities due to the historical legacy of institutional discrimination. This study highlights the importance of developing policies to combat racial inequities and how these can contribute to better oral health conditions for the older Brazilian population.